An analysis of Students Ability in Skimming and Scanning in Reading Class of English Department FTIK IAIN LANGSA - Bona Putra (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2020)
The purposes of this study were to find out the ability of students in Skimming and Scanning and to investigate how the students apply the procedure in Skimming and Scanning in Reading class. This study applied a descriptive qualitative approach. The writer used purposive sampling. The writer had nine respondents. The writer used documentation and observation as the instrument. Based on the results, indicated that in skimming, the students made a question, some also looked at the table of contents, they read or browsed at high speed, but some students were still affected to Look at reading topics. Then all students stopped when they found the topic they were looking for. but some students were not careful when text a reading. In scanning, the students also saw the table of contents first, but some students directly browsed to the page they wanted to find, besides, the students also read the background, and they also read the conclusions at a glance.